NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium 2016
DOI: 10.1109/noms.2016.7502802
|View full text |Cite
|
Sign up to set email alerts
|

An HTTP/2 push-based approach for SVC adaptive streaming

Abstract: Abstract-HTTP Adaptive Streaming (HAS) is the de facto standard for over-the-top video streaming. In HAS, video content is encoded at multiple quality levels and temporally divided into multiple segments. The client can select the quality level for every video segment, allowing smoother playback and a better Quality of Experience (QoE). Although results are promising, current solutions often suffer from high round-trip time (RTT) cycles in mobile networks. This is especially true for scalable video coding (SVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, it is not clear what was the network characteristic that the experiments were based on. In [25], the authors studied the live streaming QoE in terms of initial startup delay, buffering and quality switches. The emulation was carried out using measured LTE throughput in Belgium and included an artificial delay of up to 400ms.…”
Section: Qoe Improvement Techniques Of Http Live Streamingmentioning
confidence: 99%
“…However, it is not clear what was the network characteristic that the experiments were based on. In [25], the authors studied the live streaming QoE in terms of initial startup delay, buffering and quality switches. The emulation was carried out using measured LTE throughput in Belgium and included an artificial delay of up to 400ms.…”
Section: Qoe Improvement Techniques Of Http Live Streamingmentioning
confidence: 99%
“…A first evaluation showed promising results, such as a lower startup time and endto-end delay in high-RTT networks. In other work, we showed that the occurrence of playout freezes can be reduced through SVC-based streaming over HTTP/2, limiting the quality loss in high-RTT networks by pushing base layer segments to the client [37]. Although results are promising, the average quality is lower than for AVC-based HAS, and only a limited amount of quality layers can be used because of SVC's encoding overhead.…”
Section: Http/2 For Multimedia Deliverymentioning
confidence: 93%
“…Huysegems et al presented ten novel HTTP/2-based methods to improve the QoE of HAS [16]. Recently, van der Hooft et al introduced an HTTP/2 push-based approach for Scalable Video Coding (SVC) adaptive streaming where only the base layer of the SVC-encoded video is pushed from server to client [17]. This solution allows to eliminate one RTT cycle for every video segment, which has a significant impact on the user's QoE.…”
Section: Has Over Http/2mentioning
confidence: 99%